Improving Fishermen's Productivity and Sustainability Through Digitalization of Accounting, Marketing, and Utilization of Fisheries Science in the Segara Ayu Kedonganan Fishermen Group - Kadek Goldina Puteri DEWI; Ni Made WAHYUNI; Gede Agus Surya PRATAMA (PT Keberlanjutan Strategis Indonesia, 2025)
This community empowerment program aimed to enhance the productivity and sustainability of the Segara Ayu Kedonganan Fishermen Group by integrating digital accounting systems, digital marketing strategies, and fisheries science applications. The program addressed key challenges in financial management, marketing, and sustainable fisheries practices. The program adopted a participatory and educational approach to ensure that members of the Segara Ayu Kedonganan Fishermen Group were not merely passive recipients of assistance but were actively engaged in every stage of the process. Through a five-stage participatory approach—preparation, socialization, integrated training, field implementation, and evaluation—fishermen adopted digital financial recording, expanded online marketing channels, and improved post-harvest processing techniques. The outcomes included increased financial literacy, market access, product diversification, and environmental sustainability practices. The program also fostered collaboration between academia and local communities, contributing to the Sustainable Development Goals (SDGs) related to economic growth, responsible consumption, and life below water. The implementation of the program has proven to be highly effective in enhancing the business capacity and operational efficiency of the Segara Ayu Kedonganan Fishermen Group.